2002
DOI: 10.1007/s00431-002-0989-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional residual capacity and compliance of the respiratory system after surfactant treatment in premature infants with severe respiratory distress syndrome

Abstract: the changes in lung function following surfactant treatment can only be explained by initial stabilisation of already aerated alveoli followed by recruitment of new gas exchange units as mechanisms involved in mediating the effect of surfactant on gas exchange. However, since no significant correlation between changes in functional residual capacity and improvement in arterial-to-alveolar oxygen tension ratio was seen, other effects of surfactant must be considered. These include local and/or systemic changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…Although all infants were successfully extubated and the neuromuscular blockade was removed, the FRC values were slightly lower than that reported by VON UNGERN-STERNBERG et al [8] in intubated infants prior to anaesthetic procedures (21.3¡4.7 mL?kg -1 ). However, the infants in the present study were younger and lighter than those in the study by VON UNGERN-STERNBERG et al [8], and the present FRC values are consistent with those for ventilated pre-term infants [21,22] and nonventilated full-term control infants (18.4 mL?kg -1 ) [23].…”
Section: Neonatal Critical Care H Proquitté Et Alsupporting
confidence: 80%
“…Although all infants were successfully extubated and the neuromuscular blockade was removed, the FRC values were slightly lower than that reported by VON UNGERN-STERNBERG et al [8] in intubated infants prior to anaesthetic procedures (21.3¡4.7 mL?kg -1 ). However, the infants in the present study were younger and lighter than those in the study by VON UNGERN-STERNBERG et al [8], and the present FRC values are consistent with those for ventilated pre-term infants [21,22] and nonventilated full-term control infants (18.4 mL?kg -1 ) [23].…”
Section: Neonatal Critical Care H Proquitté Et Alsupporting
confidence: 80%
“…17 The functional residual capacity of preterm infants with RDS is significantly decreased and the reported values can vary from 6 to 10 ml kg À1 . 18,19 Future studies should address this potential risk factor. It is well known that smaller ETT have higher resistance, 20 which can contribute to decreased or slower clearance of surfactant and subsequent ETT block.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple in vivo and in vitro studies have shown a negative effect of NO on surfactant activity as well as surfactant protein gene expression (26,58). In children with elevated pulmonary vascular resistance, any decrease in pulmonary compliance due to low surfactant activity can contribute to significant morbidity (13,31). Although the relationship between NO and surfactant has been studied, the model systems used previously included primary cultures that immediately begin to undergo dedifferentiation, whole animals, and alveolar epithelial cell lines that do not express the entire type II cell phenotype.…”
mentioning
confidence: 99%